2021
DOI: 10.3788/col202119.030603
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanical dynamics of nanoimprinting anti-reflective structures onto small-core mid-IR chalcogenide fibers [Invited]

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Chalcogenide glasses (ChGs) are an ideal material with excellent mid-infrared transmission performance (at least in the 9-11 μm window), low cost, and stable manufacturing capabilities and are the only glassy materials that can cover the transmission window in the 3-12 μm wavelength range with more stable chemical properties, mature production processes, and lower costs than crystalline materials [21,22] . In addition, ChGs have the advantages of adjustable components and precision moulding, and the optical refractive index can be adjusted in the range of 2-4 by component control.…”
Section: Introductionmentioning
confidence: 99%
“…Chalcogenide glasses (ChGs) are an ideal material with excellent mid-infrared transmission performance (at least in the 9-11 μm window), low cost, and stable manufacturing capabilities and are the only glassy materials that can cover the transmission window in the 3-12 μm wavelength range with more stable chemical properties, mature production processes, and lower costs than crystalline materials [21,22] . In addition, ChGs have the advantages of adjustable components and precision moulding, and the optical refractive index can be adjusted in the range of 2-4 by component control.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the subwavelength structure with moth-eye effect has advanced anti-reflection performance [15][16][17]. At present, subwavelength structures are often fabricated by the sol-gel method [18], nanoimprinting [15,17,19], electron beam lithography [20,21], laser printing [22][23][24], etc. Moreover, researchers have found that the subwavelength LIPSS (laser-induced periodic surface structures) could be induced on the material surface by adjusting the ultrafast laser polarization shape and the external atmosphere [25][26][27].…”
Section: Introductionmentioning
confidence: 99%